MORFOGENESIS PADA DAUN, TANGKAI DAUN, DAN RUAS BATANG KENTANG HITAM (Solenostemon rotundifolius (POIR) JK MORTON) SECARA IN VITRO - Aryani Leksonowati; Witjaksono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Solenostemon rotundifolius (Poir) JK Morton is a minor crop that produce carbohydrate and therefore can be utilized for food diversifi cation and help food security program. This crop is not cultivated intensively but it is planted as a side crop during the dry season. Low yield could be responsible for its unattractiveness for farmer to farm it intensively. Improvement of varieties is needed but it is hindered by the low genetic variability due to lack of sexual reproduction. Manipulation at cell level and biotechnology could be an alternative for improving this crop. The availability of a reliable protocol(s) for plant regeneration is needed. This study is intended to develop reliable regeneration protocols using inocula derived from shoot culture on MS basal medium supplemented with various level of BA and NAA. The results show that inocula of leaf, petiole, and stem internodes respond classically to the varying concentration of sitokinin BA and auxin NAA. The optimum production of shoot that refl ect the best shoot organogenic response were achieved by leaves inoculums grew on medium supplemented with 5 mg/l BA and 0.1 mg/l NAA. This protocol serves as a protocol for further somatic cell genetic experiments to increase genetic variability of this crop.